Typographical Variants of the Brest Bible - Siess-Krzyszkowski, Stanisław (Tematy i Konteksty, 2021)
The issue that is the main focus of this paper has not been of great interest to bibliology scholars. Even though one version of the Brest Bible, marked as B, was described quite thoroughly by Feliks Bentkowski already two hundred years ago, the catalogue descriptions have until today been based upon the scheme formulated by Karol Estreicher (senior). He identified three versions of the Brest Bible, which differ only in the title page. The fact is that there are only two versions, A and B, in existence, which differ in the first gathering (*) or (very rarely) in the first two gatherings (*, **). The gatherings of version B were established to have been printed in the 1580s or 1590s in Jan Karcan’s press in Vilnius. Apparently, a certain number of the Old Testament gatherings A–Y were typeset and printed in Brest in 1563. There is only one extant complete copy of it with the newly printed gatherings, whereas in the remaining dozen or so copies that have survived it is only one, or rarely, two gatherings, and sometimes only single leaves. The search for versions of the Bible also made it possible to compile a list of 135 copies of the Brest Bible stored today in public, monastic and church collections in Europe and North America.